Successful Treatment and Secondary Prevention of Venous Thrombosis Secondary to Behçet Disease with Rivaroxaban - Ana Boban; Catherine Lambert; Cedric Hermans (Case Reports in Hematology)
We here present the successful initial treatment and secondary prophylaxis of superficial venous thrombosis secondary to Behçet’s disease by a novel anticoagulant drug, rivaroxaban (Xarelto®). To our knowledge, this is the first case of using an oral direct inhibitor of FXa in this setting. Our findings are promising; the outcome was favourable without any adverse effect noted. We propose that the patients with Behçet’s disease and venous thrombosis might benefit from the advantages of the new anticoagulant drug.